Pengaruh Variasi Ukuran dan Penempatan Void Plat Lantai terhadap Perilaku dan Kekuatan Gedung Bertingkat - Pangestuti, Pramesta Armanisag; Patria, Agustinus Sungsang Nana; Sholikhin, Ilham Putra (Universitas Batanghari Jambi, 2025)
One of the developments in the world of construction is the variety of structural system configuration types to ensure the strength, stability, efficiency, and safety of buildings. An example of a frequently encountered structural configuration variation is the presence of voids or holes in the floor slab of a building. Floor slabs that have voids affect the structural strength. This study aims to analyze the effect of variations in the size and placement of floor slab voids on the behavior and strength of multi-storey building structures. The results of the analysis are expected to be used as a reference in selecting the size and placement of floor slab voids in building planning. The building structure model analyzed is an 8-storey regular building structure with reinforced concrete materials. The height between floors is 4 meters and the total height of the building is 32 meters. The function of the building is an office located in Semarang City. The earthquake-resistant structural system used is the Special Moment Resisting Frame System (SRPMK). The floor plan size is 18x18 meters with a span between columns of 6 meters. The variations used are 6 void models with different sizes and placements. Each structural model is analyzed using ETABS software. The analysis results state that the larger the void size, the smaller the structural period, the smaller the inter-floor shear force value, and the smaller the inter-floor drift value. The recommendation for selecting the most effective size variations and void placement is in a structural model where the void is placed in the middle of the structure with the largest void size being 6x6 meters.